INNOVATIVE SOLUTIONS FOR FORMING PRESCHOOL CHILDREN'S CONCEPTS ABOUT THE SUN AND PLANETS - Xamidova Gulbahor Jizzakh State Pedagogical University Teacher of the pre-school education department. Tolliboyeva Husniya Jizzakh State Pedagogical University Student of the Preschool Education Department. (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
In this article, it is possible to see the existence of pre-school children and related events and situations aimed at loving nature. The need to explain the role of nature in child education and the need to use it rationally is emphasized, and innovative solutions for forming concepts of the sun and earth planets in preschool children are mentioned in detail. Key words: Pre-school educational institution, nature, human, role, Central Asia, thinker, protection, thought, history, introduction, method, science, innovative approaches.